TINJAUAN MAQASHID SYARIAH TERHADAP PERSELINGKUHAN SEBAGAI ALASAN POLIGAMI PADA PUTUSAN NOMOR 2982/PDT.G/2023/PA.BL - Muhammad Rafi Azzizuddin; Abd. Rouf (Al-Adl : Jurnal Hukum, 2026)
In Court Decision Number 2982/Pdt.G/2023/PA.BL, the judge stipulated that infidelity may serve as a legal basis for polygamy. Statutorily, however, such a ground is not recognized within the formal requirements for polygamy under the prevailing Marriage Law. This study examines the use of infidelity as a justification for granting polygamy permits, specifically analyzing the judge's ratio decidendi in Decision Number 2982/Pdt.G/2023/PA.BL and evaluating it through the lens of Imam al-Shatibi’s maqashid al-shari’ah. This research adopts a normative legal method with a case approach. Legal materials are derived from secondary data collected through library research. Data processing involves editing, classifying, analyzing, and concluding, while the analysis of legal materials is conducted qualitatively with a prescriptive approach. The findings demonstrate that Decision Number 2982/Pdt.G/2023/PA.BL is consistent with maqashid al-shari’ah. Regarding the core issue—polygamy on the grounds of infidelity—the petition technically fails to meet the criteria stipulated in the Marriage Law. Nevertheless, the panel of judges exercised judicial discretion, considering various dimensions and emphasizing the substantial harm (mudharat) that would ensue should the petition be rejected. Within the framework of Imam al-Shatibi’s maqashid al-shari’ah, this case intersects with four of the al-kulliyat al-khams (the five essentials): the preservation of religion (hifz al-din), life (hifz al-nafs), lineage (hifz al-nasl), and property (hifz al-mal), as an endeavor to mitigate harm and realize the welfare (maslahah) of humanity.